Efficient and Cost-Effective Alternative Treatment for Recurrent Urinary Tract Infections and Interstitial Cystitis in Women: A Two-Case Report - Anthony Mansour; Essa Hariri; Samar Shelh; Ralph Irani; Mohamad Mroueh (Case Reports in Medicine)
Urinary tract infections (UTIs) are among the most common bacterial infections affecting women. UTIs are primarily caused by Escherichia coli, which increases the likelihood of a recurrent infection. We encountered two cases of recurrent UTIs (rUTIs) with a positive E. coli culture, not improving with antibiotics due to the development of antibiotic resistance. An alternative therapeutic regimen based on parsley and garlic, L-arginine, probiotics, and cranberry tablets has been given. This regimen showed a significant health improvement and symptoms relief without recurrence for more than 12 months. In conclusion, the case supports the concept of using alternative medicine in treating rUTI and as a prophylaxis or in patients who had developed antibiotic resistance.